Azulene-Derived Fluorescent Probe for Bioimaging: Detection of Reactive Oxygen and Nitrogen Species by Two-Photon Microscopy - Murfin, Lloyd C.; Weber, Maria; Park, Sang Jun; Kim, Won Tae; Lopez-Alled, Carlos M.; McMullin, Claire L.; Pradaux-Caggiano, Fabienne; Lyall, Catherine L.; Kociok-Köhn, Gabriele; Wenk, Jannis; Bull, Steven D.; Yoon, Juyoung; et al. (Journal of the American Chemical Society, 2019)
Two-photon fluorescence microscopy has become an indispensable technique for cellular imaging. Whereas most two-photon fluorescent probes rely on well-known fluorophores, here we report a new fluorophore for bioimaging, namely azulene. A chemodosimeter, comprising a boronate ester receptor motif conjugated to an appropriately substituted azulene, is shown to be an effective two-photon fluorescent probe for reactive oxygen species, showing good cell penetration, high selectivity for peroxynitrite, no cytotoxicity, and excellent photostability.
Keywords: Cell penetration; Cellular imaging; Fluorescent probes; High selectivity; Reactive oxygen and nitrogen species; Reactive oxygen species; Two photon microscopy; Two-photon fluorescence microscopy; Azulenes; Cell Survival; Fluorescent Dyes; HeLa Cells; Humans; Limit of Detection; Microscopy, Fluorescence, Multiphoton; Reactive Nitrogen Species; Reactive Oxygen Species